Natural products: potential drugs for the treatment of renal fibrosis - Zijun Zhou; Yanheng Qiao; Yanru Zhao; Xin Chen; Jie Li; Hanqing Zhang; Qiumei Lan; Bo Yang (BMC, 2022)
Abstract With the increasing prevalence and mortality, chronic kidney disease (CKD) has become a world public health problem. As the primary pathological manifestation in CKD, renal fibrosis is often used as a critical target for the treatment of CKD and inhibits the progression of CKD to end-stage renal disease (ESRD). As a potential drug, natural products have been confirmed to have the potential as a routine or supplementary therapy for chronic kidney disease, which may target renal fibrosis and act through various pharmacological activities such as anti-inflammatory and anti-oxidation of natural products. This article briefly introduces the pathological mechanism of renal fibrosis and systematically summarizes the latest research on the treatment of renal fibrosis with natural products of Chinese herbal medicines.